Internalization of Islamic Religious Education Values in Scouting Extracurricular Activities in Forming Student Character in Public Middle School 2 Peunaron East Aceh - Zarkasyi Zarkasyi; Asnil Aidah Ritonga; Wahyudin Nur Nasution (Budapest International Research and Critics University, 2020)
This research is motivated by problems related to moral degradation that still often occurs everywhere. Various efforts from the government have been made to address this problem, one of them is by promoting character education. Many programs that have been launched by the government related to the improvement of the character of this nation, one of them through the mandatory extracurricular scout program in schools. Not only must that, learning in schools also contain character education. Mainly Islamic Religious Education as its goal is to form human beings. For this reason, the inclusion of Islamic Religious Education values in scouting activities is expected to produce quality characters, both in the mind, physical and spiritual aspects. The data of this study were compiled from residents of Public Middle School 2 Peunaron, East Aceh, who could provid Existing problems were answered through qualitative research with data collection methods such as observation, interviews, and documentation. The collected data were analyzed qualitatively by the Miles & Huberman interactive analysis model with data collection schemes, data reduction, data display and conclusions.e data related to the internalization of Islamic Education values as research objects. Existing problems were answered through qualitative research with data collection methods such as observation, interviews, and documentation. The collected data were analyzed qualitatively by the Miles & Huberman interactive analysis model with data collection schemes, data reduction, data display and conclusions.